Analysis of the Hydroponics Program in Instilling an Environmental Care Attitude for Elementary School Students - Ela Suryani; Lisa Virdinarti Putra; Na’imah Much Muf’afidah; Cholifatul Hidayah (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2020)
This study aimed to describe the planting of environmental care through hydroponic programs. This type of research is qualitative research with purposive sampling technique. The research subjects were students in grade V SDN Susukan 04 East Ungaran Semarang Regency. Data collection techniques through FGD, questionnaires, interviews, and documentation. The research instrument used was a draft FGD, questionnaire sheets, interview guides, and documentation archives. Technique validity of data through source triangulation and technique triangulation. Students carry out the hydroponic program with a floating raft system through the axis technique. The planting of an environmental care attitude is carried out through several stages of the hydroponic program, namely the stages of sowing, seedling, growth/enlarging and harvesting. The results showed that the most dominant environmental care attitude of students was nurturing plants, while the weakest environmental care attitude of students was developing a comfortable environment. The environmental care attitude that has been embedded in elementary school students is the interest in planting and caring for plants, conserving energy by using water as needed, throwing trash into the trash, and recycling used goods.